Evaluation of multiple alternative instrument platforms for targeted and non‐targeted dioxin and furan analysis. (18th April 2018) - Stultz, Conner; Jobst, Karl J.; Haimovici, Liad; Jones, Rhys; Besevic, Sladjana; Byer, Jonathan; Organtini, Kari L.; Kolic, Terry; Reiner, Eric J.; Dorman, Frank L.
Abstract: The use of gas chromatography coupled to high‐resolution magnetic sector mass spectrometers (GC‐HRMS) is well established for dioxin and furan analysis. However, the use of gas chromatography coupled to triple quadrupole (MS/MS) and time of flight (TOF) mass spectrometers with atmospheric pressure ionization (API) and traditional electron ionization (EI) for dioxin and furan analysis is emerging as a viable alternative to GC‐HRMS screening. These instruments offer greater versatility in the lab for a wider range of compound identification and quantification as well as improved ease of operation. The instruments utilized in this study included 2 API‐MS/MS, 1 traditional EI‐MS/MS, an API‐quadrupole time of flight mass spectrometer (API‐QTOF), and a EI‐high‐resolution TOF (EI‐HRTOF). This study compared these 5 instruments to a GC‐HRMS using method detection limit (MDLs) samples for dioxin and furan analysis. Each instrument demonstrated acceptable MDL values for the 17 chlorinated dioxin and furans studied. The API‐MS/MS instruments provide the greatest overall improvement in MDL value over the GC‐HRMS with a 1.5 to 2‐fold improvement. The API‐QTOF and EI‐TOF demonstrate slight increases in MDL value as compared with the GC‐HRMS with a 1.5‐fold increase. The 5 instruments studied all demonstrate acceptable MDL values with no MDL for a single congener greater than 5 times that for the GC‐HRMS. All 5 instruments offer a viable alternative to GC‐HRMS for the analysis of dioxins and furans and should be considered when developing new validated methodologies.